Analysis of the Impact of Work Motivation and Employee Commitment on Employee Performance at the Staffing Agency and Human Resource Development of the City of Solok - Nurhayati Nurhayati; Esi Sriyanti; Sarah Maidola Putri (Transpublika Publisher, 2024)
The objective of this study is to examine how work motivation and employee dedication impact the work output of employees at the Personnel and Human Resource Development Agency in Solok City. A quantitative approach was used to survey 54 participants. The statistical analysis revealed that work motivation has a partial but significant influence on work performance. This is supported by the t test results, where the value of tvalue 2.740 exceeds the critical ttable value of 2.008 at a significance level of 0.008, which is less than 0.05. It could be inferred that motivation at work plays a significant role in influencing job performance. After conducting statistical analysis, it can be deduced that the level of commitment among employees has a partial but meaningful impact on job performance within the Solok City Personnel and Human Resource Development Agency. This assertion is supported by the T test, where the t value of 4.526 surpasses the critical t value of 2.008, with a significance level of 0.000 which is lower than 0.05. Hence, it can be concluded that the commitment of employees has a significant influence on job performance. Both work motivation and employee commitment positively impact job performance at the Solok City Personnel and Human Resource Development Agency, as supported by the F test (F = 57.459, p < 0.05). The R Square value is 0.693, indicating that 69.3% of the variance in job performance is explained by these factors, with the remaining 30.7% influenced by other variables.